Behavioral Integrity: How Leader Referents and Trust Matter to Workplace Outcomes - Kannan-Narasimhan, Rangapriya (Journal of business ethics, 2012)
Behavioral integrity (BI) is the alignment pattern between an actor’s words and deeds as perceived by another person. Employees’ perception that their leader’s actions and words are consistent leads to desirable workplace outcomes. Although BI is a powerful concept, the role of leader referents, the relationship between perceived BI of different referents, and the process by which BI affects outcomes are unclear. Our purpose is to elaborate upon this process and clarify the role of different leader referents in determining various outcomes. To understand the impact of referents, we explicitly compared the BIs of two leader referents: senior management and supervisor. In contrast to previous research findings where supervisory BI was found to have a stronger relationship with outcomes than senior management, we find that both referents are important. However, their impact varies based upon the outcome studied. Only senior management BI predicted organizational commitment, while senior management BI, supervisory BI and supervisory trust predicted organizational cynicism. Only trust in supervisor, and not supervisory BI, impacted organizational citizenship behaviors. When senior management is the referent, trust and not BI might play an important role for outcomes that require extensive employee investments, such as organizational commitment. In contrast, when the outcome measured does not require employee investments, BI might have a direct impact on the outcome. We also uncovered that trust in supervisor substantially influences the trust employees have in their senior management.